Business Development Strategy of Culinary Start-Up (A Case Study of Kedai Mas Gibo) - Hamim, Muhammad Gilang Perdana; Larso, Dwi (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract. Kedai Mas GiBo as one of the business in the culinary sector, located in Bandung and was founded in 2014 until now. But after two years established, Kedai Mas GiBo’s revenue is decreasing compared to the first year. On the first year, Kedai Mas GiBo success in generating revenue about 7.000.000 – 10.000.000 IDR but on the second year, Kedai Mas GiBo’s revenue has been decreased to 3.000.000 – 5.000.000 IDR. Kedai Mas GiBo already formulates the strategy for growth, but unfortunately, its revenue was still decreasing. In this regard, this study aims to determine the important factors that should be considered in making an suitable strategy for Kedai Mas GiBo and other culinary start-ups using the Strategic Management and Business Policy with the analysis of external and internal using EFAS dan IFAS, SWOT and TOWS Matrix. The findings of this study indicate that the external factors that most affect this industry is the Indonesian people are consumptive, culinary industry is an industry that needed as a primary need, the markets are very quickly saturated for the existing trends, and many substitute product. From some external factors that most affect the industry, known that the total score of the external factor in this industry is 3.330, which means above average overall score in general and become an opportunity for Kedai Mas GiBo to growth. For the internal factors that most affect in running the business are good quality and taste of products, founders educational background is business, lack of human resources, and marketing strategy has not implemented yet. For the total score of the internal factor in Kedai Mas GiBo is 2,981, which means below the overall average score in general So, Kedai Mas GiBo needs to focus on the strengths and minimize the weaknesses of the company's internal conditions. After known some of the external and internal factors, the researchers can make some recommendations strategy for Kedai Mas GiBo based on TOWS Matrix. Recommended strategies that suitable for Kedai Mas GiBo current condition are consists of three parts, which are the corporate directional strategy, generic business strategy and functional strategy. Recommendation of corporate strategy is horizontal growth with a focus on product lines that owned by Kedai Mas GiBo. For the generic business strategy, the researcher recommends the strategy that inline with the corporate strategy which is product differentiation strategy in order to gain competitive position in the industry. In additional, researchers also recommend some functional strategy that consists of a marketing strategy, operations strategy, human resources strategy, and financial strategy. By implementing all of those strategies, the researcher expected to gain more revenue up to 25% -50% each month.Keywords: Culinary Industry, Business Development Strategy, Strategic Management, Start-up Companies